Strong surface termination dependence of the electronic structure of polar superconductor LaFeAsO revealed by nano-ARPES. (1st November 2022) - Jung, Sung Won; Rhodes, Luke C; Watson, Matthew D; Evtushinsky, Daniil V; Cacho, Cephise; Aswartham, Saicharan; Kappenberger, Rhea; Wurmehl, Sabine; Büchner, Bernd; Kim, Timur K
Abstract: The electronic structures of the iron-based superconductors have been intensively studied by using angle-resolved photoemission spectroscopy (ARPES). A considerable amount of research has been focused on the LaFeAsO family, showing the highest transition temperatures, where previous ARPES studies have found much larger Fermi surfaces than bulk theoretical calculations would predict. The discrepancy has been attributed to the presence of termination-dependent surface states. Here, using photoemission spectroscopy with a sub-micron focused beam spot (nano-ARPES) we have successfully measured the electronic structures of both the LaO and FeAs terminations in LaFeAsO. Our data reveal very different band dispersions and core-level spectra for different surface terminations, showing that previous macro-focus ARPES measurements were incomplete. Our results give direct evidence for the surface-driven electronic structure reconstruction in LaFeAsO, including formation of the termination-dependent surface states at the Fermi level. This experimental technique, which we have shown to be very powerful when applied to this prototypical compound, can now be used to study various materials with different surface terminations.